Proceedings of the Annual International Conference on Accounting Research (AICAR 2019) 2020
DOI: 10.2991/aebmr.k.200309.002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Independence, Integrity, Professionalism, and Professional Skepticism on the Accuracy of Giving Audit Opinion (The Case of Audit Board of the Republic of Indonesia)

Abstract: The purpose of the research was to explore the influence of Independence, Integrity, Professionalism and Professional Scepticism on the Accuracy of Giving Audit Opinion by Government auditors, in this case the Audit Board of the Republic of Indonesia (BPK-RI). The research seeks to broaden empirical evidence on the relationship between the influence of Independence, Integrity, Professionalism and Professional Scepticism with respect to Accuracy of Giving Audit Opinion by BPK-RI. The research using associative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 5 publications
1
5
0
2
Order By: Relevance
“…Auditor's honesty, diligence, responsibility, and objectivity enhance the integrity and must be maintained to achieve audit quality. The results confirm the second hypothesis that integrity has a positive influence on audit quality are in line with research conducted by Octaviani & Ekasari (2021); Prabowo & Suhartini (2021); Kamil & Fathonah (2020); Kertarajasa et al (2019); Hikmayah & Aswar (2019); Wardayati (2016); Bouhawia et al (2015); and Furiady & Kurnia (2015).…”
Section: 119supporting
confidence: 91%
See 2 more Smart Citations
“…Auditor's honesty, diligence, responsibility, and objectivity enhance the integrity and must be maintained to achieve audit quality. The results confirm the second hypothesis that integrity has a positive influence on audit quality are in line with research conducted by Octaviani & Ekasari (2021); Prabowo & Suhartini (2021); Kamil & Fathonah (2020); Kertarajasa et al (2019); Hikmayah & Aswar (2019); Wardayati (2016); Bouhawia et al (2015); and Furiady & Kurnia (2015).…”
Section: 119supporting
confidence: 91%
“…Researchers have shown that auditor integrity is a critical factor in the audit process and positively affects audit quality (Octaviani & Ekasari, 2021;Prabowo & Suhartini, 2021;Kamil & Fathonah, 2020;Kertarajasa et al, 2019;Hikmayah & Aswar, 2019;Wardayati, 2016;Bouhawia et al, 2015;Furiady & Kurnia, 2015).…”
Section: Impact Of Integrity On Audit Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In humanistic psychology, Carl Rogers calls it the word self as the essence of independence (Lynch and Sheldon 2017). Meanwhile, the origin of the word independent when quoting from the psychological dictionary is independence, meaning an attitude of confidence in determining decisions without depending on others (K. Kamil and Fathonah 2020). Self-confidence is an asset and strength in an individual's personality.…”
Section: The Nature Of the Curriculum Special Conditions: Independent Curriculum Hierarchymentioning
confidence: 99%
“…Independent as an attitude of not depending on others or standing firmly with self-principles without being influenced by others, meaning that there is self-autonomy in deciding or completing responsibilities (K. Kamil and Fathonah 2020). While the independent curriculum as a subject design for the autonomy of the educational institution itself that students must take from the beginning of admission to the end of entering the institution.…”
Section: Independent Curriculum Based On Islamic Valuesmentioning
confidence: 99%